1992
DOI: 10.1007/bf02342435
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of cytokines on rat islets: Evidence for involvement of free radicals and lipid peroxidation

Abstract: We have previously reported that oxygen free radical scavengers protect rat islet cells from damage by cytokines and we interpreted these findings as suggesting the involvement of oxygen free radicals but did not directly measure indices of free radical activity. In this study, we report on malondialdehyde, an end product of lipid peroxidation, in rat islets incubated with cytokines. The individual cytokines, interleukin 1 (1 U/ml), tumour necrosis factor (10(2) U/ml), and interferon gamma (10(2) U/ml) inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…Cytokines like IL-1β, IFN-γ and TNF-α have been implicated in the pathogenesis of Type I diabetes and could be a major source of free radical insult in pancreatic islet cells [5,59,60]. An effect of cytokines (IFN-γ) on expression of peroxiredoxins has been shown only in rat Kupffer cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines like IL-1β, IFN-γ and TNF-α have been implicated in the pathogenesis of Type I diabetes and could be a major source of free radical insult in pancreatic islet cells [5,59,60]. An effect of cytokines (IFN-γ) on expression of peroxiredoxins has been shown only in rat Kupffer cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that lipid peroxidation is involved in the cytotoxic effects of cytokines on rat islets and that the inhibition of this process protects islet beta cells from the combined cytotoxic effects of interleukin 1, tumor necrosis factor and interferon gamma (14). Furthermore, vitamin E has been shown to be effective in preventing severe complications in long-standing type 1 diabetic patients (15).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine treatment of pancreatic islet cells in vitro results in generation of reactive oxygen species (Rabinovitch et al 1992) and nitric oxide (Southern et al 1990). In type 1 diabetes mellitus, where islet -cells are destroyed, there is evidence of increased cytokine production (Hussain et al 1996) and formation of peroxynitrite from reactive oxygen species and nitric oxide (Suarez-Pinzon et al 1997, Lakey et al 2001) -these can contribute to cell death by both apoptosis and necrosis (Eizirik et al 1996, Hadjivassiliou et al 1998, Hoorens et al 2001.…”
Section: Introductionmentioning
confidence: 99%